Morbidly Adherent Placenta at Upper Segment of Uterus- A Case Report - Sultana, Nadira; Zahan Shoma, Arifa Akter; Alam, Khairul (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Morbidly adherent placenta (MAP) is a spectrum of disorder which describes adherence of all or part of the placenta to the uterine wall or surrounding organs. It is one of the most devastating complication of pregnancy. It occurs when there is abnormally firm attachment of placental villi to the uterine wall with the absence of normal intervening decidua basalis and nitabuch’s layer. MAP is often asymptomatic antenatally and the diagnosis is only established after unsuccessful attempt to remove of the placenta at delivery. A majority of morbidly adherent placenta are diagnosed during the third stage of labour or during caesarean section which results in adverse consequences including exsanguinating haemorrhage . It is one of the most common cause of obstetric hysterectomy. Accurate prenatal diagnosis is critical to reduce the risk of maternal morbidity and mortality. Aim: To report the case of a morbid adherent placenta at upper segment of uterus with conservation of uterus following reconstructive surgery. Case Presentation: A 24 years old 3rd gravid women with morbid adherent placenta at upper segment was treated by segmental resection and reconstructive surgery. Her post- operative period was uneventful. Conclusion: Antenatal diagnosis of morbidly adherent placenta, multi-disciplinary team with surgical expertise and facilities for blood transfusion can reduce maternal mortality and morbidity. This rare morbid attachment of placenta at upper segment is one of the example. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 157-161